POLLUTION DETECTION MODEL UTILIZING ANOMALY DETECTION TECHNIQUES PERFORMING ANALYSIS OF SATELLITE DATA (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
In this article review was created of nowadays popular way in science of working on climate change topics by processing and performing analysis of open data from Earth orbiting satellites. Open data from satellites are provided by The European Space Agency or ESA, National Aeronautics and Space Administration or NASA via portals and cloud services under their management and by other organizations via such cloud service as Creodias, for example. Open data from satellites are available for research for other topics as well, but in the scope of this article the topic of climate change is in the focus by achieving research goal and proving hypothesis that it is possible to build the pollution detection model and pollution location detection model by utilizing anomaly detection techniques and performing analysis of satellite data.